PENGARUH PENAMBAHAN INTEGRAL CRYSTALLINE WATERPROOFING TERHADAP KUAT TEKAN BETON FLY ASH F’C 35 MPA (STUDI KASUS : GEDUNG SERBAGUNA DI SURABAYA) - Agistya Rachma Larasati; Arifah Ismi Ambiya; Himatul Farichah (LPPM Universitas Abdurrab, 2026)
Concrete is one of the most widely used construction materials in infrastructure due to its high compressive strength and durability. However, concrete contains pores that significantly affect its permeability and compressive strength, which necessitates the use of admixtures or supplementary materials to enhance performance. To reduce water ingress, integral crystalline waterproofing admixtures can be incorporated. These admixtures penetrate the concrete matrix and form needle-like crystals within the pores, thereby improving impermeability and resistance to water penetration. This study aims to examine the effect of adding integral crystalline waterproofing admixture on the compressive strength of fly ash concrete with a target strength of f’c 35 MPa. The research focuses on a case study of the Multipurpose Building project in Surabaya, with comparisons made to fly ash concrete and conventional concrete. Cylindrical specimens measuring 150 mm × 300 mm were evaluated at curing ages of 7 and 14 days. The analysis utilized secondary data obtained from the project contractor, including the mix design and compressive strength test results. The findings indicate that at 7 days of curing, conventional concrete achieved the highest average compressive strength of 28.31 MPa. At 14 days, fly ash concrete with integral crystalline waterproofing demonstrated a significant improvement, reaching the highest average compressive strength of 40.82 MPa. These results highlight the variation in characteristics between different concrete mixes at different curing ages and confirm that the use of fly ash–based integral waterproofing has a substantial positive impact on compressive strength as the concrete matures.